Graphene-Based Interfaces Do Not Alter Target Nerve Cells. - Fabbro,A; Scaini,D; León,V; Vázquez,E; Cellot,G; Privitera,G; Lombardi,L; Torrisi,F; Tomarchio,F; Bonaccorso,F; Bosi,S; Ferrari,AC; et al. (ACS Nano, 2016)
Neural-interfaces rely on the ability of electrodes to transduce stimuli into electrical patterns delivered to the brain. In addition to sensitivity to the stimuli, stability in the operating conditions and efficient charge transfer to neurons, the electrodes should not alter the physiological properties of the target tissue. Graphene is emerging as a promising material for neuro-interfacing applications, given its outstanding physico-chemical properties. Here, we use graphene-based substrates (GBSs) to interface neuronal growth. We test our GBSs on brain cell cultures by measuring functional and synaptic integrity of the emerging neuronal networks. We show that GBSs are permissive interfaces, even when uncoated by cell adhesion layers, retaining unaltered neuronal signaling properties, thus being suitable for carbon-based neural prosthetic devices.